(untitled) (American Journal of Islam and Society, 1987)
Introduction A comprehensive Islamic theory that can offer complete guidance for Islamic organizations and help clarify the behavior of organizations, groups, and individuals is yet to be developed. However, there are many rules relating to administration which are scattered throughout different Islamic sources. These rules were utilized in early Islamic society, but were never organized under specific management concepts as is the case in contemporary management thought. The quest in recent years for such a theory has been intense, and there have been frantic efforts by researchers to group different administrative guidelines from Islamic sources with the intention of forming an Islamic administrative paradigm, herein called a theory, although it is not a complete theory. Ahmed Ibrahim Abu Sin, for example, has tried to identify the basic particulars or postulates of Islamic administrative theory in his book The Islamic Administration (1981). He maintains that the characteristic feature of Islamic theory is its emphasis on all the variables and factors that affect the administrative cycle in an organization and its understanding of individual behavior in light of social and cultural forces. Islamic theory sees no separation between ethics, morality, and administration. The same applies to the larger Islamic society of which administration is a subsystem. The basic postulates of Islamic theory and the variables it emphasizes include the following: (1) Islamic administrative theory should be closely connected to the social philosophy of the Islamic system and enforce the moral principles of the larger Islamic society. (This point is discussed in greater detail below.) (2) Islamic administrative theory should take into consideration economic variables and strive to fulfill individuals’ physiological needs ...